IMPLEMENTASI MEDIA PEMBELAJARAN INTERAKTIF QUIZIZZ DALAM MEMFASILITASI KETERLIBATAN SISWA KELAS VI SDN MARABAHAN 2 - Alifa Dwiyanti; Jumainah Jumainah (Universitas Tribhuwana Tunggadewi, 2026)
This study aimed to describe the implementation of the Quizizz interactive learning media in the learning process and to examine students' engagement during its use in Grade VI at SDN Marabahan 2. This study employed a qualitative approach with a descriptive research design. The participants consisted of a Grade VI teacher and Grade VI students at SDN Marabahan 2. Data were collected through observation, interviews, and documentation. Data validity was ensured through source and technique triangulation, while data were analyzed using the Miles and Huberman model, including data reduction, data display, and conclusion drawing. The findings revealed that the implementation of Quizizz was conducted through three stages: planning, implementation, and evaluation. Teachers designed learning activities according to instructional objectives, guided students during the learning process, and used quiz results for evaluation and reflection. The use of Quizizz facilitated students' engagement, as reflected in their active participation, enthusiasm, and seriousness in understanding and answering questions. Although several challenges, such as internet connectivity, technical issues, and differences in students' abilities, were encountered, teachers addressed them through guidance, motivation, and reflective learning. Therefore, Quizizz effectively supports student engagement and promotes active, interactive, and student-centered learning.